2010
DOI: 10.1530/rep-09-0503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of linoleic acid on bovine oocyte maturation and embryo development

Abstract: Linoleic acid (LA; 18:2 n-6) is the most abundant fatty acid in bovine follicular fluid, and it was previously reported that LA concentration significantly decreases when follicle size increases. This suggests that LA may have a role in the regulation of oocyte maturation. The present study investigated the effect of LA supplementation on bovine oocyte maturation and early embryo development in vitro. Treatment of cumulus-oocyte complexes (COCs) with LA significantly inhibited cumulus cell expansion and retard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 55 publications
5
109
1
5
Order By: Relevance
“…The primer set used was also able to detect other C members (AKR1C1 and AKR1C4), producing the same PCR product size. Since this study group has previously detected PGF 2a in spent media at 24 h of bovine oocyte maturation (Marei et al, 2010), this suggests that PGFS in COC belong to a different isoform. Other enzymes like AKR1B5 have been identified as functional PGFS in bovine endometrium (Madore et al, 2003) and may be functional in COC as well.…”
Section: Discussionmentioning
confidence: 72%
“…The primer set used was also able to detect other C members (AKR1C1 and AKR1C4), producing the same PCR product size. Since this study group has previously detected PGF 2a in spent media at 24 h of bovine oocyte maturation (Marei et al, 2010), this suggests that PGFS in COC belong to a different isoform. Other enzymes like AKR1B5 have been identified as functional PGFS in bovine endometrium (Madore et al, 2003) and may be functional in COC as well.…”
Section: Discussionmentioning
confidence: 72%
“…In the former study, alteration of PUFAs through the dietary sources of FAs led to improvement of oocyte development potential [7]. In bovine species, supplementation of maturation medium with essential fatty acids has been shown to have positive [3] or negative [4] effects on oocyte developmental competence depending on the type of fatty acid studied.…”
Section: Introductionmentioning
confidence: 97%
“…Previous reports have shown that supplementary fatty acids have significant effects on oocyte maturation and subsequent pre-implantation development [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bilby et al (2005Bilby et al ( , 2006 reported that dairy cows given a diet enriched with linoleic acid tended to yield aspirated oocytes with a subsequently slower rate of in vitro embryo development than those from cows given an oleic acid-enriched diet. Linoleic acid supplementation of an in vitro culture medium (Marei et al, 2010) confirmed its inhibitory effect on bovine oocytes and early embryos. In contrast, the same group had previously found that supplementation with α-linolenic acid enhanced maturation rate and increased bovine blastocyst yield (Marei et al, 2009).…”
Section: Introductionmentioning
confidence: 83%